PROFIL TINGKAT KECANDUAN GAME ONLINE PESERTA DIDIKKELAS XMA PLUS AL MUJAMMIL GARUT - IIK IKBAL; Wikanengsih Wikanengsih; Muhamad Rezza Septian (IKIP Siliwangi, 2021)
The purpose of this study was to determine the level of addiction to online games of class X MA Plus Al Mujammil Cisurupan Garut. The method used is descriptive quantitative research with data collection tools on the scale of online game addiction and student observation sheets in the classroom. The results showed that the level of students' online game addiction was in the non-addictive category 38.5%, mild addiction 15.3% and severe addiction 46.2%. The results of the study on the level of student addiction if addiction is not handled properly it can lead to uncontrolled students because they are not able to reduce playing time so that social relations and tasks are hampered. Keywords: : Online Game Addiction, Students